A carbon nanotube-based sound-absorbing flocculent carbon material, its preparation method and application

By attaching nanopore particles to carbon nanotubes and carbonizing at high temperatures to form floc carbon materials, combined with porous and resonant sound absorption mechanisms, the problem of limited absorption effects of existing sound absorption materials in different frequency bands is solved, and efficient, stable and environmentally friendly sound absorption performance is achieved.

CN114822466BActive Publication Date: 2025-06-10QILU NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210359256.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-07
Publication Date
2025-06-10
Estimated Expiration
2042-04-07

AI Technical Summary

Technical Problem

The existing sound-absorbing materials have limited acoustic wave absorption effects in different frequency bands, and the thickness and bulkiness of traditional materials lead to inconvenient installation and decoration, and are costly and poor environmentally friendly.

Method used

The sound-absorbing carbon material based on carbon nanotubes is used to form nanopore particles through hybrid bimetal and organic coordination, adhere to the carbon nanotubes, and form the mass-absorbing carbon material through high-temperature carbonization, combining the porous and resonant sound absorption mechanism to achieve high-efficiency sound absorption performance at high and low frequencies.

Benefits of technology

It realizes a material with high-efficiency sound absorption performance in different frequency bands of high and low frequency. It has a stable material structure, a long service life, easy to fill and make various shapes, and is environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114822466B_ABST
    Figure CN114822466B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes, comprising the following steps: mixing two or more metal salts and dissolving them in deionized water to form solution A; mixing deionized water, ethanol, and N,N-dimethylformamide to prepare a mixed solvent, and dissolving 1H-pyrazole-4-carboxylic acid, 2,5-dihydroxy-1,4-benzoquinone or fumaric acid in the above-mentioned mixed solvent to form solution B; mixing solution A and solution B, putting them into a microwave chemical reactor, and reacting to obtain solid powder as nano-porous particles; attaching the nano-porous particles to carbon nanotubes and performing high-temperature carbonization in a non-oxidizing atmosphere to prepare the flocculent carbon material. The present invention also provides the sound-absorbing flocculent carbon material prepared by the preparation method. The combination of the porous sound-absorbing mechanism and the resonance sound-absorbing mechanism is realized, and high-efficient sound-absorbing performance is achieved in different frequency bands of high frequency and low frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sound absorption and noise reduction, and particularly relates to a sound-absorbing flocculent carbon material based on carbon nanotubes, a preparation method thereof, and an application thereof. Background Art

[0002] At present, sound-absorbing materials have developed rapidly in the fields of household, automotive, construction, etc. With the continuous efforts of researchers, the performance of non-woven sound-absorbing materials has become increasingly excellent, largely meeting the needs of society. However, there is still no material that can completely absorb sound waves in different frequency bands. To better improve the sound-absorbing performance of sound-absorbing materials, efforts should be made on the basis of combining the porous sound-absorbing mechanism and the resonance sound-absorbing mechanism. Through the research on the composite process of porous sound-absorbing materials and resonance sound-absorbing materials, it can effectively achieve high-efficiency sound-absorbing performance in different frequency bands of high frequency and low frequency. At the same time, combined with the inherent characteristics of sound waves, by mixing different raw materials and combining different non-woven processes, the unique three-dimensional structure of non-woven materials can be fully utilized to prepare high-efficiency sound-absorbing materials that meet the diverse performance requirements of materials. Of course, more efforts should be made for the development of sound-absorbing materials in line with the requirements of low material cost, high-quality products, environmental friendliness, etc.

[0003] Most sound-absorbing materials are loose and porous materials, such as slag wool, blankets, etc. Their sound-absorbing mechanism is that sound waves penetrate into the pores of the material, and most of the pores are open pores that communicate with each other inside. Subject to the friction and viscous resistance of air molecules, and causing the fine fibers to vibrate mechanically, thereby converting sound energy into heat energy. The sound-absorbing coefficient of such porous sound-absorbing materials generally increases gradually from low frequency to high frequency, so the absorption effect on high-frequency and medium-frequency sounds is better. According to the different structures of the materials, sound-absorbing materials can be divided into three categories: porous, resonance, and special structures. Currently, porous sound-absorbing materials are the most widely used, mainly including four categories: organic fibers, inorganic fibers, inorganic foams, and foam plastics.

[0004] The sound-absorbing materials filled in the sound insulation interlayer of a music room will greatly improve its sound insulation effect. However, the sound-absorbing performance of traditional materials such as sound-absorbing cotton and sound-absorbing boards is limited. In order to achieve the expected sound insulation effect, this results in a larger thickness of the interlayer, occupying more indoor space, and the thick-sized sound insulation interlayer is very heavy, bringing great inconvenience and difficulties to installation and decoration. Therefore, how to provide a sound-absorbing material with outstanding sound-absorbing performance, small mass density, easy to fill, long service life, and no addition of any additives or adhesives during the production process has become an urgent need. Summary of the Invention

[0005] In view of the defects and problems in the prior art, the present invention provides a sound-absorbing flocculent carbon material based on carbon nanotubes and a preparation method thereof. The sound-absorbing material forms nano-porous particles by hybridizing bimetals and organic ligands, which are attached to a carrier with a carbon nanotube as the skeleton. The carbon nanotube carrier has a mesoporous and macroporous structure, and a flocculent carbon material is formed by in-situ composite through high-temperature carbonization. The combination of the porous sound-absorbing mechanism and the resonance sound-absorbing mechanism is realized, and high-efficiency sound-absorbing performance is achieved in different frequency bands of high frequency and low frequency.

[0006] The present invention provides an application of the material in the sound-absorbing material filled in the sound insulation interlayer of a music room.

[0007] The technical solution adopted by the present invention to achieve the above object is as follows:

[0008] A preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes, comprising the following steps:

[0009] (1) Mix two or more metal salts and dissolve them in deionized water to form solution A;

[0010] (2) Mix deionized water, ethanol, and N,N-dimethylformamide to prepare a mixed solvent, and dissolve 1H-pyrazole-4-carboxylic acid, 2,5-dihydroxy-1,4-benzoquinone, or fumaric acid in the above mixed solvent to form solution B;

[0011] (3) Mix solution A and solution B, put them into a microwave chemical reactor, and react to obtain solid powder as nano-porous particles;

[0012] (4) Attach the nano-porous particles to the carbon nanotubes and perform high-temperature carbonization in a non-oxidizing atmosphere to obtain the flocculent carbon material.

[0013] Further, the metal salt is a cobalt salt, a manganese salt, an iron salt, or an aluminum salt, and the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube.

[0014] Furthermore, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate, or cobalt carbonate; the manganese salt is manganese nitrate, manganese chloride, manganese acetate, manganese sulfate, or manganese carbonate; the iron salt is iron nitrate, iron chloride, iron acetate, or iron sulfate; the aluminum salt is aluminum nitrate, aluminum chloride, aluminum acetate, aluminum sulfate, or aluminum carbonate.

[0015] Further, the molar ratio of the metal salt to 1H-pyrazole-4-carboxylic acid, 2,5-dihydroxy-1,4-benzoquinone, or fumaric acid is 1:0.5 to 2, and the mass ratio of the nano-porous particles to the carbon nanotubes is 1:0.1 to 50; the volume ratio of deionized water, ethanol, and N,N-dimethylformamide is 0.5 to 5:1:0.5 to 5.

[0016] Further, the reaction conditions in step (3) are as follows: irradiated under microwave of 1 kW and microwave frequency of 800 - 5000 MHz, heated to 105 - 200 °C, and maintained at 105 - 200 °C and 0.1 - 1 Mpa for reaction for 20 - 120 min.

[0017] Furthermore, the reaction conditions are as follows: irradiated under microwave of 1 kW and microwave frequency of 2400 MHz, heated to 130 °C, and maintained at 130 °C and 0.18 Mpa for reaction for 30 min.

[0018] Further, the method for the nano - pore particles to adhere to the carbon nanotubes is the impregnation method, the electrostatic adsorption method or the coating method.

[0019] Further, the non - oxidative atmosphere is N 2 2, CO 2 or NH 3 3. More preferably, the non - oxidative atmosphere is NH 3 3.

[0020] Further, the high - temperature carbonization temperature is 650 °C - 1000 °C. More preferably, the high - temperature carbonization temperature is 750 °C.

[0021] The present invention discloses the sound - absorbing flocculent carbon material prepared by the above - described preparation method.

[0022] The present invention discloses the application of the sound - absorbing flocculent carbon material in the sound - absorbing material filled in the sound - insulation interlayer of a music room.

[0023] In this application, the sound - absorbing flocculent carbon material includes:

[0024] A support material;

[0025] The support material is loaded with carbon derived from nano - pore particles;

[0026] Among them, the support material is a carbon nanotube.

[0027] The carbon nanotube carrier has mesoporous and macroporous structures. After attaching nano - pore particles and undergoing high - temperature carbonization, it can enable the carbon derived from nano - pore particles to grow in situ on the surface of the carbon nanotubes, forming a flocculent carbon material. This can not only enhance the void structure of the material, but also greatly improve the structural strength of the material and reduce the difficulty of the carbon material production process. Compared with traditional carbon materials, the flocculent carbon material of the present invention not only has better sound - absorbing performance; at the same time, the metal structure in the nano - pore particles can form a strong absorption capacity for low - frequency sound waves, enabling the carbon material to have better low - frequency noise absorption ability. After the obtained flocculent composite structure undergoes high - temperature carbonization heat treatment, the metal atoms will not fall off due to the vibration of the deformed sound wave and have excellent sound - absorbing stability.

[0028] Beneficial effects

[0029] (1) The preparation method of this application has the characteristic of a simple carbonization process. During the preparation process, no additives or adhesives are added, and the environmental protection benefits are obvious.

[0030] (2) During the preparation process of this application, the nano-porous particle-derived carbon is in-situ grown on the surface of the carbon nanotubes. The flocculent carbon material has a stable structure and a long service life. At the same time, the metal atoms in the nano-porous particles are retained in the flocculent carbon material, which can further improve the material's absorption ability for low-frequency noise.

[0031] (3) The sound-absorbing flocculent carbon material prepared in this application is extremely easy to fill and can be made into various shapes according to different needs. At the same time, the material will not rot and can resist the corrosion of various microorganisms, fungi, acids, salts, and hydrocarbons. The material is odorless and does not contain any harmful substances such as formaldehyde. It has good waterproof, moisture-proof, and breathable properties.

[0032] (4) The operation method of this application is simple, low-cost, and has universality, making it easy to scale up production. Description of the Drawings

[0033] Figure 1 It is a scanning electron microscope image of a sound-absorbing flocculent carbon material based on carbon nanotubes prepared in Example 1 of the present invention.

[0034] Figure 2 It is a scanning electron microscope image of a sound-absorbing flocculent carbon material based on carbon nanotubes prepared in Example 2 of the present invention.

[0035] Figure 3 It is a scanning electron microscope image of a sound-absorbing flocculent carbon material based on carbon nanotubes prepared in Example 3 of the present invention.

[0036] Figure 4 It is a schematic diagram of the filling structure of the sound-absorbing material of the present invention.

[0037] Figure 5 It is a performance comparison curve graph of the sound-absorbing materials of Examples 1-3 and Comparative Examples 1-3 and glass fiber felt of the present invention.

[0038] In the figure, 1 is the filled sound-absorbing material sandwich layer, 2 is the 2-mm-thick glass fiber felt, and 3 is the 2-mm-thick glass fiber felt for sealing the four sides. Detailed Embodiments

[0039] To facilitate understanding of the details and essence of the present invention, the following further describes specific embodiments.

[0040] Example 1

[0041] A preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes is as follows:

[0042] (1) Dissolve aluminum nitrate nonahydrate (7 mmol) and cobalt nitrate hexahydrate (3 mmol) in 100 ml of deionized water, and continuously stir until all the metal salts are dissolved, denoted as solution A;

[0043] (2) Mix deionized water (50 mL), ethanol (50 mL), and N,N-dimethylformamide (50 mL) to prepare a mixed solvent, and dissolve 1H-pyrazole-4-carboxylic acid (12 mmol) in the above solvent until completely dissolved, denoted as solution B;

[0044] (3) Add solution A to solution B, and under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, and stir for 30 minutes until there is no precipitate to obtain a mixed solution C;

[0045] (4) Transfer the obtained mixed solution C to a microwave reaction kettle. The inner tank of the reaction kettle is made of polytetrafluoroethylene material, and the outer tank is made of p-poly(phenylene) material. Place the microwave reaction kettle in a low-temperature and low-pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 130 °C, the pressure is 0.18 MPa, and the heating time is 30 minutes. Continuously carry out low-temperature and low-pressure reactions under microwave irradiation;

[0046] (5) After the reaction kettle naturally cools to room temperature (25 °C), filter the obtained solid product and wash it once with N,N-dimethylformamide. Continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, stir for 30 minutes, and centrifuge at 4000 revolutions per minute for 20 minutes to obtain a solid;

[0047] (6) Immerse the obtained solid product in methanol twice, each immersion time is 30 minutes, and centrifuge at 4000 revolutions per minute for 20 minutes; then wash it once with ethanol, once with deionized water, and once with ethanol again. After each washing, centrifuge at 4000 revolutions per minute for 20 minutes;

[0048] (7) Place the obtained solid product in a vacuum oven for constant-temperature drying. The vacuum pressure is 0.08 MPa, the temperature is 125 °C, and dry for 12 hours to finally obtain a nano-porous particle powder containing aluminum-cobalt bimetallic atoms;

[0049] (8) Disperse the above-mentioned particles in 100 ml of ethanol solution, continuously stir to form a suspension, and keep no precipitation. Weigh carbon nanotubes according to the mass ratio of particles to carbon nanotubes of 1:20 and slowly add them to the above suspension. Continuously stir. After all the ethanol solution has evaporated, put the obtained solid into an oven and dry it at 120 °C for 4 hours; put the above solid into a tubular furnace, and introduce N at a flow rate of 200 ml / min 2 , sinter at 750 °C for 4 hours. The finally obtained black powder is the sound-absorbing flocculent carbon material.

[0050] Example 2

[0051] A preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes, the specific steps are as follows:

[0052] (1) Dissolve manganese chloride tetrahydrate (6 mmol) and ferric sulfate nonahydrate (4 mmol) in 200 ml of deionized water, continuously stir until all the metal salts are dissolved, and record it as solution A;

[0053] (2) Mix deionized water (50 mL), ethanol (50 mL), and N,N-dimethylformamide (100 mL) to prepare a mixed solvent. Dissolve 2,5-dihydroxy-1,4-benzoquinone (16 mmol) in the above solvent until all are dissolved, and record it as solution B;

[0054] (3) Add solution A to solution B, under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, and the stirring time is 30 minutes until there is no precipitation to obtain a mixed solution C;

[0055] (4) Transfer the obtained mixed solution C to a microwave reaction kettle. The inner tank of the reaction kettle is made of polytetrafluoroethylene material, and the outer tank is made of p-phenylphenol material. Place the microwave reaction kettle in a low-temperature and low-pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 150 °C, the pressure is 0.15 MPa, and the heating time is 60 minutes. Continuously carry out low-temperature and low-pressure reactions under microwave irradiation;

[0056] (5) After the reaction kettle naturally cools to room temperature (25 °C), filter the obtained solid product and wash it once with N,N-dimethylformamide. Continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, stir for 30 minutes, and centrifuge at 4000 revolutions per minute in a centrifuge for 20 minutes to obtain a solid;

[0057] (6) To remove the residual organic solvents in the synthesis process, the obtained solid product was soaked in methanol twice, with each soaking time being 30 min, centrifuged at 4000 revolutions per minute in a centrifuge for 20 min; then washed once with ethanol, once with deionized water, and once again with ethanol, and centrifuged at 4000 revolutions per minute in a centrifuge for 20 min after each washing;

[0058] (7) The obtained solid product was placed in a vacuum oven for constant-temperature drying, with a vacuum pressure of 0.08 MPa, a temperature of 125 °C, and dried for 12 h, finally obtaining nano-porous particle powder containing manganese and iron bimetallic atoms;

[0059] (8) The above-mentioned particles were dispersed in 100 ml of ethanol solution, continuously stirred to form a suspension, ensuring no precipitation. According to the mass ratio of particles to carbon nanotubes of 1:20, carbon nanotubes were weighed and slowly added to the above suspension, continuously stirred. After all the ethanol solution had evaporated, the obtained solid was placed in a drying oven and dried at 120 °C for 4 hours; the above solid was placed in a tubular furnace, and N 2 was introduced at a flow rate of 200 ml / min, sintered at 750 °C for 4 hours, and the finally obtained black powder was the sound-absorbing flocculent carbon material.

[0060] Example 3

[0061] A preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes, the specific steps are as follows:

[0062] (1) Dissolve aluminum nitrate nonahydrate (5 mmol) and ferric sulfate nonahydrate (5 mmol) in 200 ml of deionized water, continuously stir until all the metal salts are dissolved, and record it as solution A;

[0063] (2) Mix deionized water (50 mL), ethanol (50 mL), and N,N-dimethylformamide (100 mL) to prepare a mixed solvent, and dissolve fumaric acid (20 mmol) in the above solvent until completely dissolved, and record it as solution B;

[0064] (3) Add solution A to solution B, under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, and stir for 30 min until no precipitation occurs, obtaining a mixed solution C;

[0065] (4) Transfer the obtained mixed solution C into a microwave reactor. The inner tank of the reactor is made of polytetrafluoroethylene and the outer tank is made of p-polyphenol. Place the microwave reactor in a low-temperature and low-pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 150 °C, the pressure is 0.15 MPa, and the heating time is 60 min. Continuously carry out the reaction under low temperature and low pressure under microwave irradiation;

[0066] (5) After the reactor naturally cools to room temperature (25 °C), filter the obtained solid product and wash it once with N,N-dimethylformamide. Continuously heat it in a water bath at 70 °C, stir at 800 revolutions per minute for 30 min, centrifuge in a centrifuge at 4000 revolutions per minute for 20 min to obtain a solid;

[0067] (6) In order to remove the residual organic solvents in the synthesis process, soak the obtained solid product in methanol twice, with each soaking time being 30 min, centrifuge in a centrifuge at 4000 revolutions per minute for 20 min; then wash it once with ethanol, once with deionized water, and then once with ethanol. After each washing, centrifuge in a centrifuge at 4000 revolutions per minute for 20 min;

[0068] (7) Place the obtained solid product in a vacuum oven for constant-temperature drying. The vacuum pressure is 0.08 MPa, the temperature is 125 °C, and dry for 12 h to finally obtain nano-porous particle powder containing manganese and iron bimetallic atoms;

[0069] (8) Disperse the above particles in 100 ml of ethanol solution, continuously stir to form a suspension, and keep no precipitation. Weigh carbon nanotubes according to the mass ratio of particles to carbon nanotubes of 1:20 and slowly add them to the above suspension, continuously stir. After all the ethanol solution has evaporated, put the obtained solid into a drying oven and dry it at 120 °C for 4 hours; put the above solid into a tube furnace, introduce N2 at 200 ml / min, sinter at 750 °C for 4 hours, and the finally obtained black powder is the sound-absorbing flocculent carbon material.

[0070] Comparative Example 1

[0071] A preparation method of a sound-absorbing carbon material of iron element-loaded carbon nanotubes, the specific steps are as follows:

[0072] (1) Dissolve ferric nitrate nonahydrate (10 mmol) in 200 ml of deionized water, continuously stir, and under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute for 30 min until there is no precipitation to obtain a mixed solution, denoted as solution A;

[0073] (2) Transfer the obtained Solution A to a microwave reactor. The inner tank of the reactor is made of polytetrafluoroethylene, and the outer tank is made of p-polyphenol. Place the microwave reactor in a low-temperature and low-pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 150 °C, the pressure is 0.15 MPa, and the heating time is 60 min. Continuously carry out the reaction under low temperature and low pressure under microwave irradiation;

[0074] (3) After the reactor is naturally cooled to room temperature (25 °C), filter the solid product obtained by drying Solution A and wash it once with N,N-dimethylformamide. Continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute for 30 min, and centrifuge at 4000 revolutions per minute in a centrifuge for 20 min to obtain a solid;

[0075] (6) In order to remove the residual organic solvents in the synthesis process, soak the obtained solid product in methanol twice, with each soaking time being 30 min, and centrifuge at 4000 revolutions per minute in a centrifuge for 20 min; then wash it once with ethanol, once with deionized water, and then once with ethanol. After each washing, centrifuge at 4000 revolutions per minute in a centrifuge for 20 min;

[0076] (7) Place the obtained solid product in a vacuum oven for constant-temperature drying. The vacuum pressure is 0.08 MPa, the temperature is 125 °C, and the drying time is 12 h. Finally, obtain the nano-porous particle powder containing iron element;

[0077] (8) Disperse the above particles in 100 ml of ethanol solution, continuously stir to form a suspension, and keep no precipitation. According to the mass ratio of particles to carbon nanotubes of 1:20, weigh the carbon nanotubes and slowly add them to the above suspension, continuously stir. After all the ethanol solution has evaporated, put the obtained solid into a drying oven and dry it at 120 °C for 4 hours; put the above solid into a tube furnace, and introduce N 2 , sinter at 750 °C for 4 hours. The finally obtained black powder is the sound-absorbing carbon material of iron element-loaded carbon nanotubes.

[0078] Comparative Example 2

[0079] A preparation method of a sound-absorbing carbon material of manganese element-loaded carbon nanotubes, the specific steps are as follows:

[0080] (1) Dissolve manganese acetate dihydrate (10 mmol) in 100 ml of deionized water, continuously stir, and under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, and the stirring time is 30 min until there is no precipitation to obtain a mixed solution, denoted as Solution A;

[0081] (2) Transfer the obtained Solution A to a microwave reactor. The inner tank of the reactor is made of polytetrafluoroethylene and the outer tank is made of p - polyphenol. Place the microwave reactor in a low - temperature and low - pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 150 °C, the pressure is 0.15 MPa, and the heating time is 60 min. Continuously carry out the low - temperature and low - pressure reaction under microwave irradiation;

[0082] (3) After the reactor naturally cools to room temperature (25 °C), filter the solid product obtained by drying Solution A and wash it once with N,N - dimethylformamide. Continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute for 30 min, centrifuge at 4000 revolutions per minute in a centrifuge for 20 min to obtain a solid;

[0083] (6) In order to remove the residual organic solvents in the synthesis process, soak the obtained solid product in methanol twice, with each soaking time being 30 min, centrifuge at 4000 revolutions per minute in a centrifuge for 20 min; then wash it once with ethanol, once with deionized water, and then once with ethanol. After each washing, centrifuge at 4000 revolutions per minute in a centrifuge for 20 min;

[0084] (7) Place the obtained solid product in a vacuum oven for constant - temperature drying. The vacuum pressure is 0.08 MPa, the temperature is 125 °C, and the drying time is 12 h. Finally, obtain the nano - porous particle powder containing iron elements;

[0085] (8) Disperse the above - mentioned particles in 100 ml of ethanol solution, continuously stir to form a suspension, and keep no precipitation. According to the mass ratio of particles to carbon nanotubes of 1:20, weigh the carbon nanotubes and slowly add them to the above - mentioned suspension, continuously stir. After all the ethanol solution has evaporated, put the obtained solid into a drying oven and dry it at 120 °C for 4 hours; put the above - mentioned solid into a tubular furnace, introduce N 2 , sinter at 750 °C for 4 hours. The finally obtained black powder is the sound - absorbing carbon material of manganese - element - loaded carbon nanotubes.

[0086] Comparative Example 3

[0087] A preparation method of an aluminum - cobalt - element - loaded sound - absorbing floc - like carbon material based on carbon nanotubes, and the specific steps are as follows:

[0088] (1) Dissolve aluminum nitrate nonahydrate (27 mmol) and cobalt nitrate hexahydrate (3 mmol) in 100 ml of deionized water, continuously stir until all the metal salts are dissolved, and record it as Solution A;

[0089] (2) Mix deionized water (50 mL), ethanol (50 mL), and N,N-dimethylformamide (50 mL) to prepare a mixed solvent. Dissolve 1H-pyrazole-4-carboxylic acid (1 mmol) in the above solvent until completely dissolved, and label it as solution B.

[0090] (3) Add solution A to solution B. Under the action of an ultrasonic power of 2 kW and a frequency of 40 kHz, continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, and stir for 30 minutes until there is no precipitate to obtain a mixed solution C.

[0091] (4) Transfer the obtained mixed solution C to a microwave reaction kettle. The inner tank of the reaction kettle is made of polytetrafluoroethylene material, and the outer tank is made of p-phenylphenol material. Place the microwave reaction kettle in a low-temperature and low-pressure microwave chemical reactor. The microwave power is 1 kW, the microwave frequency is 2400 MHz, heat to 130 °C, the pressure is 0.18 MPa, and heat for 30 minutes. Continuously carry out low-temperature and low-pressure reactions under microwave irradiation.

[0092] (5) After the reaction kettle naturally cools to room temperature (25 °C), filter the obtained solid product and wash it once with N,N-dimethylformamide. Continuously heat in a water bath at 70 °C, stir at 800 revolutions per minute, stir for 30 minutes, and centrifuge at 4000 revolutions per minute for 20 minutes to obtain a solid.

[0093] (6) Immerse the obtained solid product in methanol twice, each immersion time is 30 minutes, and centrifuge at 4000 revolutions per minute for 20 minutes; then wash it once with ethanol, once with deionized water, and once with ethanol again. After each washing, centrifuge at 4000 revolutions per minute for 20 minutes.

[0094] (7) Place the obtained solid product in a vacuum oven for constant-temperature drying. The vacuum pressure is 0.08 MPa, the temperature is 125 °C, and dry for 12 hours to finally obtain nano-porous particle powder containing aluminum and cobalt bimetallic atoms.

[0095] (8) Disperse the above particles in 100 ml of ethanol solution, continuously stir to form a suspension, keep no precipitate formed, weigh carbon nanotubes according to the mass ratio of particles to carbon nanotubes of 1:20, and slowly add them to the above suspension. Continuously stir. After all the ethanol solution has evaporated, put the obtained solid into a drying oven and dry at 120 °C for 4 hours; put the above solid into a tube furnace, and introduce N 2 , sinter at 750 °C for 4 hours, and the finally obtained black powder is the sound-absorbing flocculent carbon material.

[0096] Performance Testing

[0097] As a sound-absorbing material for filling the sound insulation interlayer of a music practice room, the sound-absorbing mass-flecked carbon materials prepared in the above-mentioned examples and comparative examples were filled between two 2-mm-thick fiberglass felts, with a filling thickness of 10 mm, and the four sides were sealed with 2-mm-thick fiberglass felts. For comparison, five 2-mm-thick fiberglass felts without improvement were stacked with a filling thickness of 10 mm. A sound absorption measurement was carried out by the standing wave tube method, and the results are shown in Table 1. It can be seen from the table that in the low-frequency range of 125 - 1000 Hz, the sound absorption performance was significantly improved.

[0098] Table 1 Sound Absorption Test Results

[0099]

[0100] Finally, it should be noted that the above are only the preferred embodiments of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or perform equivalent replacements for some of them. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes, characterized in that, it comprises the following steps: (1) Mix two or more metal salts and dissolve them in deionized water to form solution A; (2) Mix deionized water, ethanol, and N,N-dimethylformamide to prepare a mixed solvent, and dissolve 1H-pyrazole-4-carboxylic acid, 2,5-dihydroxy-1,4-benzoquinone, or fumaric acid in the above mixed solvent to form solution B; (3) Mix solution A and solution B, put them into a microwave chemical reactor, react to obtain solid powder as nano-porous particles; (4) Attach the nano-porous particles to carbon nanotubes and perform high-temperature carbonization in a non-oxidizing atmosphere to obtain the flocculent carbon material.

2. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the metal salt is cobalt salt, manganese salt, iron salt or aluminum salt, and the carbon nanotube is single-walled carbon nanotube or multi-walled carbon nanotube.

3. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 2, characterized in that, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate or cobalt carbonate; the manganese salt is manganese nitrate, manganese chloride, manganese acetate, manganese sulfate or manganese carbonate; the iron salt is iron nitrate, iron chloride, iron acetate, iron sulfate; the aluminum salt is aluminum nitrate, aluminum chloride, aluminum acetate, aluminum sulfate or aluminum carbonate.

4. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the molar ratio of the metal salt to 1H-pyrazole-4-carboxylic acid, 2,5-dihydroxy-1,4-benzoquinone or fumaric acid is 1:0.5-2, and the mass ratio of the nano-porous particles to the carbon nanotubes is 1:0.1-50; the volume ratio of deionized water, ethanol, and N,N-dimethylformamide is 0.5-5:1:0.5-5.

5. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the reaction conditions in step (3) are under microwave irradiation of 1 kW and microwave frequency of 800-5000 MHz, heating to 105-200 °C, and maintaining the reaction at 105-200 °C and 0.1-1 Mpa for 20-120 min.

6. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the method for attaching the nano-porous particles to the carbon nanotubes is the impregnation method, the electrostatic adsorption method or the coating method.

7. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the non-oxidizing atmosphere is N2, CO2 or NH3.

8. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 1, characterized in that, the temperature of the high-temperature carbonization is 650 °C - 1000 °C.

9. The preparation method of a sound-absorbing flocculent carbon material based on carbon nanotubes according to claim 8, characterized in that, the temperature of the high-temperature carbonization is 750 °C.

10. An acoustic flocculent carbon material prepared by the preparation method according to any one of claims 1-9.

11. Use of the acoustic flocculent carbon material according to claim 10 in a sound-absorbing material filled in a sound-insulating interlayer of a music room.

Citation Information

Patent Citations

  • Method for preparing nano-composite material of carbon nano-tube and hydroxyapatite with growth in situ

    CN101318034A

  • Sound absorbing device and system thereof

    CN107025904A